Nociceptin/orphanin FQ opioid peptide‐receptor expression in pachyonychia congenita. Issue 4 (16th October 2018) - Pan, Baohan; Schröder, Wolfgang; Jostock, Ruth; Schwartz, Mary; Rosson, Gedge; Polydefkis, Michael
Abstract : Nociceptin/orphanin FQ opioid peptide (NOP)‐receptor (NOP‐R) is a member of the opioid receptor family. NOP‐R activation has demonstrated analgesic effects in preclinical pain models without the addiction risks associated with other opiate targets. Pachyonychia congenita (PC) is a palmoplantar keratoderma characterized by neuropathic pain in affected skin. A cohort of KRT6A gene mutation PC patients with no other explanation for their neuropathic pain offered a unique opportunity to assess potential of NOP‐R as a therapeutic target. Plantar biopsies from 10 PC patients and 10 age/gender matched controls were performed at the ball (PC‐affected) and the arch (PC‐unaffected) of the foot. NOP‐R expression was assessed by immunohistochemistry. Localization of NOP‐R in subsets of epidermal nerve fibers was investigated using the pan‐neuronal marker PGP9.5, markers for unmyelinated peptidergic fibers (calcitonin gene‐related peptide [CGRP] and substance P [SP]), as well as for myelinated Aδ and Aβ fibers (neurofilament H [NFH]). Robust NOP‐R expression was detected in epidermal keratinocytes and in a subset of PGP9.5+ fibers in both epidermis and dermis, confirmed by western blot and absorption experiments with NOP‐R peptide. NOP‐R expression in keratinocytes was significantly reduced in PC‐affected plantar skin compared with PC‐unaffected skin. In addition, NOP‐R expression occurred in dermal NFH+ myelinated fibers in all groups, although few CGRP+ fibers co‐expressed NOP‐R. Furthermore, most SP+ fibers also co‐expressed NOP‐R. These findings indicate that NOP‐R is expressed on epidermal keratinocytes, as well as on epidermal and dermal nerve fibers and has potential as a promising target to treat neuropathic pain in PC.